Tudo é e não é: poder e ironia no sertão rosiano - Antunes, Joeli teixeira (2023)
This work presents the doctoral research entitled Everything is and is not: power and irony in the Rosiano backlands. The object of analysis corresponds to the study of the narrative “Buriti”, which is part of the set of novels of Corpo de Baile, by João Guimarães Rosa, published in 1956. It has as objective to show the various facets of power that run through the personal relationships established among the residents of the Buriti Bom farm and the countryside people of that place, in addition to showing that, through a refined irony, Guimarães Rosa elaborates scenes of the countryside people daily life. With this, the research problem was constituted from the following questions: considering that, against the grain of power and oppression structures, Guimarães Rosa gives voice to silenced subaltern subjects, how do power relations and irony appear in “Buriti”? By inserting different voices in his texts, does the author denounce prejudices, misunderstandings and hasty judgments in the context of this narrative? To answer such questions it was resorted to a critical-bibliographical research and it was applied the hypothetical-deductive method, based on “Buriti” and critical fortune on the narrative. In order to understand the concept of power/power relations were analyzed the theoretical-critical propositions elaborated by Michel Foucault, constants in the works History of Sexuality I (1988), Microphysics of power (1979) and The order of discourse (2005), as well as a reading on the reflections of Pierre Bourdieu, in The Symbolic Power (1998), among others. From this, the reflections on the concept of irony occurred through the realization of a historical/critical/literary journey based on the books: Irony and the Ironic(1995), by Douglas Colin Muecke; The dialect of fragments (1997), by Friedrich Schlegel; Theory and Politics of Irony (2000), by Linda Hutcheon; Problems of the Poetics of Dostoyevsky (1981), by Mikhail Bakhtin, in addition to the thesis entitled Machado de Assis and Irony: style and worldview (2006), by Andrea Czarnobay Perrot. Instigated by these reading concerns, the hypothesis of this research is that, in “Buriti”, irony can be found in power relations, in the lines of resistance, in the subjectivity of the subjects and in their creator process. It is concluded that in the Rosiano backlands the space of the narrative is centered on a rural environment that allows perceiving possibilities of multiple interpretation of the sertaneja region, which is not imprisoned in an archetype; rather, it considers the presence of interdictions permeating the manor house, the farm and the rural structure. In this way, the sertão exists as a space for the representation of patriarchalism, clientelism, power relations, all of which can be analyzed through irony, which in “Buriti” corresponds to a way of subverting authority and questioning the surrounding world, allowing individuals to express their subjectivity and establish a critical relationship with it, since irony allows the presence of several different points of view and voices in an enunciation. In the Rosiano backlands, “is” is not opposite to what “is not”; one does not imply the erasure of the other, but rather the explicitness of criticism via the subject in a contesting attitude: ironic.